Ekstrak n-Heksana Daun Maja (Aegle marmelos) Menurunkan Kadar LDL Mencit Diabetes yang Diinduksi Aloksan (n-Hexane Extract of Maja Leaves (Aegle marmelos) Decreases LDL Levels on Diabetic Mice Induced by Alloxan) - Lesti Eko Pangestuti; Fifteen Aprila Fajrin; Diana Holidah (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Diabetes mellitus is a metabolic disorder which characterized by hyperglicaemia due to abnormalities of carbohydrate, fat an protein metabolism resulting from defects in insulin secretion, insulin action or both. Metabolic disorders are caused by diabetes induce lipolysis, resulting in changes in the levels of LDL in the blood. This research aims to know the effect of n-hexane extract of maja leaves in LDL levels in diabetic mice. Test animals were induced by alloxan 210 mg/kg BW intraperitoneally. Twenty five mice were divided into 5 groups, control negative group (CMC Na 1%), control positive group (glibenclamide suspension 0.65 mg/kg BW), and the treatment group was given 3 suspension of of n-hexane extract of maja leaves (dose of 200 mg/kg BW, 400 mg/kg BW, and 800 mg/kg BW) for 14 days. The result showed that the decrease of LDL level due to N-hexane extracts of maja leaves dose 200 mg/kg BW, 400 mg/kg BW, and 800 mg/kg BW was -10,54%; 9,07%; 31,69%; respectively. N-hexane extracts of maja leaves decreases LDL levels on diabetic mice induced by alloxan with the best activity indicated by doses 800 mg/kg BW. Keywords: Aegle marmelos, n-hexane, diabetes melitus, LDL, alloxan